2014
DOI: 10.1007/s10439-014-1117-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systems View of Risk Factors for Knee Osteoarthritis Reveals Insights into the Pathogenesis of the Disease

Abstract: Early detection of osteoarthritis (OA) remains a critical yet unsolved multifaceted problem. To address the multifaceted nature of OA a systems model was developed to consolidate a number of observations on the biological, mechanical and structural components of OA and identify features common to the primary risk factors for OA (aging, obesity and joint trauma) that are present prior to the development of clinical OA. This analysis supports a unified view of the pathogenesis of OA such that the risk for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
112
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(115 citation statements)
references
References 54 publications
2
112
0
1
Order By: Relevance
“…Therefore, the differences in strain between the regions are likely due to differences in the collagen network structure. These regional differences in internal mechanical environment under the same applied load and nominal strain suggest a sensitivity of cartilage to shifts in the location of applied joint load and support the hypothesis that altered gait kinematics may be a mechanism to cartilage degeneration [13].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Therefore, the differences in strain between the regions are likely due to differences in the collagen network structure. These regional differences in internal mechanical environment under the same applied load and nominal strain suggest a sensitivity of cartilage to shifts in the location of applied joint load and support the hypothesis that altered gait kinematics may be a mechanism to cartilage degeneration [13].…”
Section: Discussionsupporting
confidence: 67%
“…This suggests a potential pathway to degeneration following altered knee kinematics [13], which likely shift the regions of high load from the central region to the peripheral region [11,14,44]. Previous studies have demonstrated differences in biomechanical properties between regions [8,17,45], but did not analyze the internal strain fields in isolated regions of cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,23,24 It has been suggested that these kinematic changes shift the location of repetitive joint contact loads during walking to regions of cartilage not conditioned for these loads because of regional variations in both cartilage structure and biology. 3,8,9 If the new region of cartilage cannot adapt to the change in repetitive loading during ambulation, a degenerative pathway ensues. 4,5,10,23,27 …”
mentioning
confidence: 99%
“…While insidious degeneration results in a common end‐point, a non‐functional articulation, the initiating causes or mechanisms are often unclear. For the homeostasis or health of the joint stability of the system arises as a function of the integrated behavior of the biological, mechanical, and structural elements of the system 20. In Chu et al,21 an apt analogy is made between the probability of developing OA and the alignment of biological, mechanical, and structural factors as a slot/fruit machine.…”
Section: Biology As a Systemmentioning
confidence: 99%